2016
DOI: 10.1097/ajp.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Do Pain-related Beliefs Influence Adherence to Multidisciplinary Rehabilitation?

Abstract: The findings suggest that treatment adherence is determined by a combination of pain-related beliefs either supporting or inhibiting chronic pain patients' ability to adhere to treatment recommendations over time. In the studies reviewed, self-efficacy appears to be the most commonly researched predictor of treatment adherence, its effects also influencing other pain-related beliefs. More refined and standardized methodologies, consistent descriptions of pain-related beliefs, and methods of measurement will im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 105 publications
4
28
0
Order By: Relevance
“…When viewed at the bivariate level, pain self-efficacy (at pre-and post-intervention) was the only significant correlate of post-intervention treatment adherence. This finding is consistent with other research (Brus, van de Laar, Taal, Rasker, & Wiegman, 1999;Medina-Mirapeix et al, 2009;Thompson et al, 2016), which has also found a link between pain self-efficacy and post-intervention treatment adherence. Notably, the adherence and pain self-efficacy correlation was only marginally larger for post-treatment than pre-treatment self-efficacy despite observed improvements in pain self-efficacy by post-intervention.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…When viewed at the bivariate level, pain self-efficacy (at pre-and post-intervention) was the only significant correlate of post-intervention treatment adherence. This finding is consistent with other research (Brus, van de Laar, Taal, Rasker, & Wiegman, 1999;Medina-Mirapeix et al, 2009;Thompson et al, 2016), which has also found a link between pain self-efficacy and post-intervention treatment adherence. Notably, the adherence and pain self-efficacy correlation was only marginally larger for post-treatment than pre-treatment self-efficacy despite observed improvements in pain self-efficacy by post-intervention.…”
Section: Discussionsupporting
confidence: 93%
“…Despite considerable exploration of the influence of psychological factors on prognosis in chronic pain contexts, few studies have explored the impact of these factors on treatment adherence, particularly in the post-treatment maintenance phase (Thompson et al, 2016). The present longitudinal study sought to remedy this by testing the predictive value of four previously identified psychological risk factors (fear-avoidance, pain self-efficacy, depression, and anxiety) for post-intervention treatment adherence following a pain management intervention.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this sense, there has been a growing recognition that the degree of chronic pain is influenced by the beliefs, attitudes and expectations of individuals. [27][28][29] Given the importance of pain as a mechanism of survival, it is perhaps unsurprising that pain perception is clearly influenced by conscious and unconscious memory, cognitive and emotional functioning and contextual factors that are explicitly included in a biopsychosocial formulation of pain. 30 Inside of the biopsychosocial understanding of chronic pain, there is a growing interest, and acceptance in hypothesising that the association between physical impairment, pain intensity and pain-related disability is only moderate and that psychological factors may influence the experience of pain and its impact and hence may play a crucial role in the maintenance of pain-related problems.…”
Section: Introductionmentioning
confidence: 99%